A study on the impact of the communicative approach to grammar teaching on students' interest at the Institute of Foreign Language-Hanoi University of Agriculture - Nguyễn, Thị Hiên (University of Languages and International Studies, 2017)
This study is an attempt to look into the matter of how Communicative Language Teaching is applied in teaching grammar at IFL -HUA and the impact of CLT on students’ interest in grammar learning.It is believed that the insights into these areas will help to address the matter of teaching grammar effectively at universities and at foreign language centers as well. To achieve the aims of the thesis, the following questions were proposed: 1. What is the fact of grammar teaching and learning at IFL – HUA? 2. To what extent does CLT affect students’ interest in the context of IFL – HUA?